A study on the anatomy features of green and dark brown buffalo leech (Hirudinea Manillensis) - Zulhisyam Abdul Kari @ Abdullah; Mohd Hafiz Jamaludin; Shazani Sarijan; Mohammad Amizi Ayob; Lee Seong Wei; Mohd Sukhairi Mat Rasat; Mazlan Mohamed; Muhammad Iqbal Ahmad; Ahmad Anwar Ismail; Nik Nur Azwanida Zakaria; M.Marwan; M. Farhan (Universiti Malaysia Terengganu, 2014)
Leeches (Phylum: Annelida, Class: Hirudinea) are widely distributed all over the world